2015
DOI: 10.3174/ajnr.a4280
|View full text |Cite
|
Sign up to set email alerts
|

Negative Susceptibility Vessel Sign and Underlying Intracranial Atherosclerotic Stenosis in Acute Middle Cerebral Artery Occlusion

Abstract: BACKGROUND AND PURPOSE:The role of MR imaging in predicting underlying intracranial atherosclerotic stenosis before endovascular stroke therapy has not been studied. Our aim was to determine the diagnostic value of the negative susceptibility vessel sign on T2*-weighted gradient-echo MR imaging for predicting underlying intracranial atherosclerotic stenosis in patients with acute MCA occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 22 publications
3
25
1
Order By: Relevance
“…In this study, clots with a GRE SVS showed significantly lower IL‐1 β , TNF‐ α and MMP‐9 expression compared to clots without an SVS. These results support the idea that a GRE SVS is more frequently observed in patients with cardiogenic embolic stroke than in those with other stroke subtypes3, 12 and clots with a negative SVS could be associated with atherosclerosis 3, 13. The T2‐shortening effect of the intracellular deoxyhemoglobin component in red blood cells within the clot is the pathophysiologic basis of an SVS 3.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…In this study, clots with a GRE SVS showed significantly lower IL‐1 β , TNF‐ α and MMP‐9 expression compared to clots without an SVS. These results support the idea that a GRE SVS is more frequently observed in patients with cardiogenic embolic stroke than in those with other stroke subtypes3, 12 and clots with a negative SVS could be associated with atherosclerosis 3, 13. The T2‐shortening effect of the intracellular deoxyhemoglobin component in red blood cells within the clot is the pathophysiologic basis of an SVS 3.…”
Section: Discussionsupporting
confidence: 82%
“…It was previously established that the presence of an SVS on GRE imaging was markedly associated with a higher red blood cell count in the clot, whereas fibrin‐dominant clots were associated with the absence of an SVS 3, 12. Fibrin‐dominant clots are typically formed because of endothelium injury overlies the complicated plaque in the setting of advanced atherosclerosis 13. Therefore, fibrin‐dominant clots related to advanced atherosclerosis would not appear as an SVS on GRE imaging due to the lack of deoxyhemoglobin, and could have increased expression of cytokines, matrix‐degrading proteases, or other inflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations